2022
DOI: 10.1038/s41598-022-14199-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic analysis of Streptomyces rapamycinicus NRRL 5491 and its mutant overproducing rapamycin

Abstract: Streptomyces rapamycinicus NRRL 5491 is a well-known producer of rapamycin, a secondary metabolite with useful bioactivities, including antifungal, antitumor, and immunosuppressive functions. For the enhanced rapamycin production, a rapamycin-overproducing strain SRMK07 was previously obtained as a result of random mutagenesis. To identify genomic changes that allowed the SRMK07 strain’s enhanced rapamycin production, genomes of the NRRL 5491 and SRMK07 strains were newly sequenced in this study. The resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…As exemplified by S. rimosus and other Streptomyces species, both the frequency and scale of rearrangements can also be induced by mutagenesis or genetic engineering ( 50 , 54 ). Jo et al ( 55 ) demonstrated that a rapamycin-overproducing strain of Streptomyces rapamycinicus , generated by random mutagenesis and strain selection for higher production of rapamycin, underwent spontaneous genome reduction: the 12.47 Mb genome of the native parent strain was reduced to 9.56 Mb in the overproducing strain. A larger gene deletion near one chromosomal end was accompanied by a DNA duplication, containing the entire BGC encoding biosynthesis of rapamycin.…”
Section: Discussionmentioning
confidence: 99%
“…As exemplified by S. rimosus and other Streptomyces species, both the frequency and scale of rearrangements can also be induced by mutagenesis or genetic engineering ( 50 , 54 ). Jo et al ( 55 ) demonstrated that a rapamycin-overproducing strain of Streptomyces rapamycinicus , generated by random mutagenesis and strain selection for higher production of rapamycin, underwent spontaneous genome reduction: the 12.47 Mb genome of the native parent strain was reduced to 9.56 Mb in the overproducing strain. A larger gene deletion near one chromosomal end was accompanied by a DNA duplication, containing the entire BGC encoding biosynthesis of rapamycin.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure for analyzing neoaureothin concentrations was based on a previous study (Peng et al, 2019). Packed mycelium volume was used for biomass determination (Jo et al, 2022; Wu et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Edison et al [31] used in-silico analysis in structural elucidation. Some researchers used comparative genomics in their studies [32][33][34][35][36][37]. Kumar et al [38] used in vitro and insilico analysis using machine learning in their studies.…”
Section: Streptomyces Lividans -Streptomyces Coelicolor Andmentioning
confidence: 99%